Nausea-Vomiting and Anorexia in Post-Chemotherapy Patients - Gustini Gustini; Tintin Sukartini; Ilya Krisnana (FORIKES, 2019)
Introduction: Some studies show that post-chemotherapy cancer patients experience nausea vomiting and anorexia, in RSUP Dr. Wahidin Sudirohusodo also found difficulties with nausea vomiting and anorexia. Aims: To the study was to prevent vomiting of nausea and anorexia in cancer patients after chemotherapy. Methods: 60 post-chemotherapy cancer patients who experienced nausea vomiting and anorexia were included in a crosssectional study. The selected subject fulfills the criteria. Study inclusion: Patients diagnosed with cancer in the Lontara 2 Chemotherapy Room. Patients who have received chemotherapy, adjuvant chemotherapy and additional chemotherapy, are ≥ 21 years old. Nausea and vomiting were measured using the INVR questionnaire and anorexia using a history of anorexia questionnaire. Data were analyzed using descriptive analysis. Results: based on the characteristics of respondents nausea and anorexia vomiting distributed 41-50 years, female sex, secondary school education, working as a housewife, cycles 1-4 times. Conclusion: Cancer patients after chemotherapy experience vomiting of nausea and anorexia. Nausea vomiting is caused by the effects of chemotherapy drugs which stimulate the digestive system, causing moderate and severe nausea and anorexia. Keywords: nausea; vomiting; anorexia; cancer; chemotherapy ABSTRAK Pendahuluan: Beberapa studi menunjukkan pasien kanker pasaca kemoterapi mengalami mual muntah dan anoreksia, di RSUP Dr. wahidin Sudirohusodo juga ditemukan mengalami mual muntah dan anoreksia. Tujuan: untuk mengidentifikasi mual muntah dan anoreksia pada pasien kanker pasca kemoterapi. Metode: 60 pasien kanker pasca kemoterapi yang mengalami mual muntah dan anoreksia dilibatkan dalam penelitian crosssectional. Mual muntah dinilai menggunakan kuesioner INVR dan anoreksia menggunakan kuesioner riwayat anoreksia. Data dianalisis dengan menggunakan analisis deskriptif. Hasil: berdasarkan karakteristik responden yang mengalami mual muntah dan anoreksia mayoritas berusia 41-50 tahun, berjenis kelamin perempuan, berpendidikan sekolah menengah atas, bekerja sebagai IRT, siklus kemoterapi 1-4 kali. Kesimpulan: Mayoritas pasien kanker pasca kemoterapi mengalami mual muntah dan anoreksia. Mual muntah ini terjadi karena efek obat kemoterapi dapat meransang sistem gastrointestinal yang menyebabkan terjadinya mual muntah sedang dan berat serta mengalami anoreksia. Kata kunci: mual; muntah; anoreksia; kanker; kemoterapi